IMPLEMENTATION OF TECHNOLOGY AND INFORMATION DEVELOPMENTS IN IMPROVING INDONESIAN EDUCATION - Fitriansyah, Aswin (Yayasan Meira Visi Persada, 2024)
This research aims to analyze the implementation of technological and information developments in enhancing education in Indonesia. Using a qualitative descriptive method, this study concludes that the current educational landscape actively leverages technological and information advancements to improve the quality of national education. One crucial step in enhancing the quality of national education involves revitalizing the learning processes. The integration of technology, information, and communication plays a significant role in the learning phases. The utilization of technology, information, and communication can stimulate students' creativity during the learning process. Besides serving as a learning tool, technology, information, and communication can also be used to distribute teaching materials and facilitate communication in the learning process. Thus, the comprehensive use of technology, information, and communication contributes significantly to improving the quality of education in Indonesia.